IDIOMS, PROVERBS, AND METAPHORS: CULTURAL REFLECTIONS IN LANGUAGE - Zarifakhon Makhmudova; Eldorbek Khamitov (Modern American Journals, 2025)
This article examines idioms, proverbs, and metaphors as culturally embedded elements of language, focusing on their usage and significance in Uzbek, Russian, and English literary traditions. These figurative expressions serve not only as stylistic devices but also as cultural signposts, reflecting the historical experiences, moral values, and worldviews of their respective societies. Through a comparative analysis of selected literary texts, the study reveals how similar themes—such as wisdom, morality, human relationships, and nature—are expressed differently across cultures due to unique metaphorical frameworks and idiomatic conventions. Particular attention is given to the challenges of interpreting and translating these culturally nuanced expressions, which often resist direct equivalence in cross-cultural communication. The findings highlight the importance of cultural literacy and contextual awareness in both literary analysis and translation practices. Research aims to deepen our understanding of how language not only shapes communication but also carries the weight of cultural heritage, offering a bridge for intercultural dialogue and literary appreciation.
Keywords: Uzbek, Russian and English language, translation, literature, idioms, metaphors, literary expressions, traditions.